The Influence of User Education on Students’ Ability to Utilize the Services of the UPT Library at UIN Walisongo - Rizky Sulistyowati, Novia Amanda (UIN Raden Intan Lampung, 2025)
This study aims to determine the impact of the user education program at the Library of the State Islamic University (UIN) Walisongo, specifically to assess the students' ability to utilize library services. User education is intended to provide guidance and knowledge to library users so that they can effectively utilize the library's information services and facilities. This study employs a quantitative method with data collected from 189 respondents, students of the Faculty of Science and Technology at UIN Walisongo. The research results show that the impact of user education falls into the category of positive but not significant. The indicator of interest in the user education program has the highest mean score (3.2), while the appropriate time allocation has the lowest mean score (3.18). The affective indicator (attitudes and behavior) on the Y variable has the highest mean score (3.38), categorized as very good, while the psychomotor indicator (ability) has the lowest mean score (3.16), categorized as good. These findings indicate that although students have a high interest in the user education program, their ability to utilize library services is still not optimal. The conclusion of this study highlights the need for improvements in the user education program, particularly in terms of time allocation and enhancing students' psychomotor abilities so that the program can be more effective in helping students optimally utilize library resources.